2011
DOI: 10.1258/ebm.2011.011207
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol induced epigenetic perturbations during the inflammatory stage of fracture healing

Abstract: It is well recognized by orthopedic surgeons that fractures of alcoholics are more difficult to heal successfully and have a higher incidence of non-union, but the mechanism of alcohol's effect on fracture healing is unknown. In order to give direction for the study of the effects of alcohol on fracture healing, we propose to identify gene expression and microRNA changes during the early stages of fracture healing that might be attributable to alcohol consumption. As the inflammatory stage appears to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 102 publications
(108 reference statements)
0
17
0
1
Order By: Relevance
“…Similarly, the proliferation of keratinocytes, key to re-epithelialization of wound surfaces, is regulated by epigenetic factors (Rafehi et al, 2011). Moreover, alcoholics have a higher risk of nonunion after bone fractures, and this has been linked to epigenetic changes affecting cell migration, proliferation and differentiation (Sampson et al, 2011). Zeybel and co-workers investigated whether these epigenetic traits might be handed down through generations, and in a rat model of liver damage, they found that the fibrogenic component of liver damage was still alleviated in the first-and secondgeneration offspring after ancestral chronic liver injury induced by carbon tetrachloride (Zeybel et al, 2012).…”
Section: Wound Healingmentioning
confidence: 99%
“…Similarly, the proliferation of keratinocytes, key to re-epithelialization of wound surfaces, is regulated by epigenetic factors (Rafehi et al, 2011). Moreover, alcoholics have a higher risk of nonunion after bone fractures, and this has been linked to epigenetic changes affecting cell migration, proliferation and differentiation (Sampson et al, 2011). Zeybel and co-workers investigated whether these epigenetic traits might be handed down through generations, and in a rat model of liver damage, they found that the fibrogenic component of liver damage was still alleviated in the first-and secondgeneration offspring after ancestral chronic liver injury induced by carbon tetrachloride (Zeybel et al, 2012).…”
Section: Wound Healingmentioning
confidence: 99%
“…Outside the brain, alcohol exposure also alters miRNA expression and function associated with gut leakiness and liver damage (Tang et al, 2008), steato-hepatitis (Dolganiuc et al, 2009), inflammation (Bala & Szabo, 2012), fibrosis (Meng et al, 2012), and bone remodeling (Sampson et al, 2011). In an early study exemplifying the promise of miRNAs for understanding alcoholism-associated disease, Tang and colleagues showed, in a gut epithelial monolayer model, that alcohol induced miR-212 expression while decreasing expression of the target tight-junction complex protein ZO-1.…”
Section: Mirnas As Mediators Of Ethanol Effects In Developing and Adumentioning
confidence: 99%
“…In 2007, we showed that miRNAs were sensitive to alcohol [19] and mediated alcohol effects on fetal neural [19, 20] and cranial development [21] in animal models. MiRNAs play an important role in alcohol addiction [2226] and neurotoxicity [27], alcohol-associated alterations in intestinal and hepatic integrity [28, 29], inflammation [30], fibrosis [31], and bone remodeling [32]. Thus, miRNAs are not only sensitive to alcohol exposure, but also mediate many alcohol effects.…”
Section: Introductionmentioning
confidence: 99%